Selective metallic coating of 3D-printed microstructures on flexible substrates. Issue 81 (7th November 2017) - Huang, Kuan-Ming; Tsai, Shang-Chen; Lee, Yu-Kuan; Yuan, Cheng-Kai; Chang, Yu-Ching; Chiu, Hsien-Lung; Chung, Tien-Tung; Liao, Ying-Chih
Abstract : In this work, a simple method was developed to fabricate micron scale three-dimensional (3D) conductive objects on a flexible PDMS substrate. Abstract : In this work, a simple method was developed to fabricate micron scale three-dimensional (3D) conductive objects on a flexible PDMS substrate. 3D microstructures were fabricated by the two photon polymerization (TPP) technique and metalized by a subsequent electroless plating step. The PDMS substrate was pre-treated with plasma to develop temporary compatible wettability of the photopolymerizable resin Ormocomp monomer. After the TPP fabrication, hydrophilic 3D microstructures were printed and adhered well to the PDMS surfaces, which recovered hydrophobicity after the TPP process. The printed 3D microstructures were then activated and immersed in an electroless copper plating bath. Due to the hydrophilicity differences, conformal conductive coatings were selectively and uniformly deposited on the 3D microstructures. Several 3D metallic microstructures with complex shapes were demonstrated to show the potential aspects of applying this technology for flexible 3D conductive objects.